The WEBT campaign to observe AO 0235+16 in the 2003-2004 observing season : Results from radio-to-optical monitoring and XMM-Newton observations - Romero, Gustavo Esteban (2005)
A multiwavelength campaign to observe the BL Lac object AO 0235+16 (z = 0.94) was set up by the Whole Earth Blazar Telescope (WEBT) collaboration during the observing seasons 2003-2004 and 2004-2005, involving radio, near-IR and optical photometric monitoring, VLBA monitoring, optical spectral monitoring, and three pointings by the XMM-Newton satellite. Here we report on the results of the first season, which involved the participation of 24 optical and near-IR telescopes and 4 radio telescopes, as well as the first XMM-Newton pointing, which occurred on January 18-19, 2004. Unpublished data from previous epochs were also collected (from 5 optical-NIR and 3 radio telescopes), in order to fill the gap between the end of the period presented in Raiteri et al. (2001) and the start of the WEBT campaign. The contribution of the southern AGN, 2 arcsec distant from the source, is taken into account. It is found to especially affect the blue part of the optical spectrum when the source is faint. In the optical and near-IR the source has been very active in the last 3 years, although it has been rather faint most of the time, with noticeable variations of more than a magnitude over a few days. In contrast, in the radio bands it appears to have been "quiescent" since early 2000. The major radio (and optical) outburst predicted to peak around February-March 2004 (with a six month uncertainty) has not occurred yet. When comparing our results with the historical light curves, two different behaviours seem to characterize the optical outbursts: only the major events present a radio counterpart. The X-ray spectra obtained by the three EPIC detectors are well fitted by a power law with extra-absorption at z = 0.524; the energy index in the 0.2-10 keV range is well constrained: α = 0.645 ± 0.028 and the 1 keV flux density is 0.311 ± 0.008 μJy. The analysis of the X-ray light curves reveals that no significant variations occurred during the pointing. In contrast, simultaneous dense radio monitoring with the 100 m telescope at Effelsberg shows a ∼2-3% flux decrease in 6-7 h, which, if intrinsic, would imply a brightness temperature well above the Compton limit and hence a lower limit to the Doppler factor δ ≳ 46. We construct the broad-band spectral energy distribution of January 18-19, 2004 with simultaneous radio data from Effelsberg, optical data from the Nordic Optical Telescope (NOT), optical-UV data from the Optical Monitor onboard XMM-Newton, and X-ray data by the EPIC instruments. Particular care is taken to correct data for extinction due to both the Milky Way and the z = 0.524 absorber. The resulting SED suggests the existence of a bump in the UV spectral region.